Der Nutri-Score: Eine quantitative Studie zur Wirksamkeit visuellen Nudgings auf das Konsumentenverhalten - Yvette Skretkowicz; Jens K. Perret (Books on Demand (BoD), 2023)
Globally, unhealthy diets have a significant impact on people's risk of disease and mortality, so the German Ministry of Nutrition and Agriculture also focuses on healthier and balanced diets in its reduction and innovation strategy. By means of the NutriScore, the nudging principle is used to provide consumers with additional nutritional labeling and to encourage the purchase of healthy foods. The aim of this study is to investigate the effectiveness of visual nudging in FMCGs in the form of the Nutri-Score on consumers' purchase decisions and to validate its robustness with respect to the demographic factors of gender and age. For this purpose, an online survey was conducted with 296 participants and the purchase behavior of selected products, before and after insertion of the Nutri-Score, was examined. A multinomial logistic regression analysis showed that purchasing behavior changed with the insertion of the Nutri-Score, with subjects avoiding negatively rated products and preferring positively rated products. It was further shown that these effects persist regardless of the age and gender of the subjects.
Keywords: 650; Ernährungspolitik; Ernährungsverhalten; Produktinformation; Warenkennzeichnung; Kaufentscheidung; Nudge; Wirkungsanalyse; Stichprobenerhebung; Deutschland; Ernährungspolitik; Ernährungsverhalten; Produktinformation; Warenkennzeichnung; Kaufentscheidung; Nudge; Wirkungsanalyse; Stichprobenerhebung; Deutschland